A survey on cost effective optical network unit configurations - Mohamed, Ibrahim M M (Penerbit Universiti Kebangsaan Malaysia, 2021)
The technology of Wavelength division multiplexing-Passive optical networks WDM-PONs is basically developed based on the approach of broadcast-and-select in which an identical aggregation of wavelengths is directed to different destinations using a power splitter. Later, it was developed based on the approach of wavelength routing in which an aggregation of wavelengths is separated and directed in such a way that each individual wavelength in the aggregation can reach a specific destination using an arrayed waveguide grating (AWGs). It is one of the highly nominated technologies for next-generation optical access network NG-OAN. This is due to its ability to overcome the limitation imposed in the currently standardized TDM-PONs (E-PON, G-PON, 10G-EPON, and XG-PON), such as their shared-traffic nature and allowable power budget. However, the inventory of wavelength-specific transmitters needed in this technology especially at subscriber premises (i.e. optical network unit ONU) where cost is most sensitive, and their associated operation, administration, and management costs remains a major issue that needs to be settled before widespread commercial success can be achieved. This attracts many researchers to concentrate their efforts to develop a cost-effective ONU. Many proposals were found in the literature that aims to realize this desirable goal with most of them agreed up on that it can be achieved by enabling ONU mass production. They also agreed up on that enabling the ONU mass production can only be achieved by unifying its design. In this paper, the author provides a review of various state-of-the-art configurations, proposed to unify the ONU design.